Daya Saing Karet Alam Indonesia Dan Perkembangan Ekspor Karet Alam Indonesia Dengan Thailand - Aulia Fajriyah; Daspar; Wahyuningrum; Finky Damayanti; Fadilla Ayu Nirma (Jurnal Ekonomi dan Bisnis Digital, 2024)
Indonesia and Thailand are the two largest countries as the world's leading suppliers of natural rubber. And by looking at opportunities to find potential markets in order to maintain balanced trade relations with developed countries. This study aims to analyze the development strategy of Indonesia's natural rubber exports with Thailand efficiently and effectively. In this study, using a qualitative method system from references to previous journal sources. Based on previous research conducted, it shows the difference in the amount of natural rubber production and synthetic rubber, as well as the competitiveness of natural rubber exports between Indonesia and Thailand. And the level of development